Expatriates' Performance Profiles: Examining the Effects of Work Experiences on the Longitudinal Change Patterns. (February 2019) - Takeuchi, Riki; Li, Yixuan; Wang, Mo
Using four-wave, longitudinal, archival data sets from an expatriate sample (237 engineers and 191 managers) working in China, we explore whether different performance change patterns exist for expatriates during their international assignments and how work-related experiences accumulated prior to the assignments relate to performance change patterns. Using a latent class growth analysis, we identify the coexistence of four distinct longitudinal change patterns of expatriate job performance (i.e., u-curve, learning-curve, stable high-performance, and stable low-performance patterns). Further, we demonstrate that three different types of prior work experiences (i.e., international, job, and organizational) are important antecedents of such performance change patterns. Specifically, expatriates with moderate levels of work experiences displayed a u-curve pattern, expatriates with a high level of international work experience but low levels of job and organizational experiences displayed a learning-curve pattern, expatriates with an abundance of work experiences started off with a high level of job performance and maintained this performance level over the course of the international assignment, and expatriates with insufficient work experiences started off with a low level of job performance and were unable to improve their performance during the course of their international assignments. This set of findings contributes to the expatriation literature by highlighting the coexistence of multiple subgroups with different performance-change patterns based on prior work experiences and providing an effective integration of the social learning perspective and the human capital accumulation perspective.